A hybrid ultrasonic membrane anaerobic system (UMAS) development for palm oil mill effluent (POME) treatment - Nour, A. H.; Rosli, Mohd Yunus; Nour, Azhari Hamid; Hayder, Gasim; Norasyikin, Ismail (MDPI, 2023)
The high chemical oxygen demand (COD) and biochemical oxygen demand (BOD) levels in palm oil mill effluent (POME) wastewater make it an environmental contaminant. Moreover, conventional POME wastewater treatment approaches pose economic and environmental risks. The present study employed an ultrasonic membrane anaerobic system (UMAS) to treat POME. Resultantly, six steady states were procured when a kinetic assessment involving 11,800–21,700 mg·L−1 of mixed liquor suspended solids (MLSS) and 9800–16,800 mg·L−1 of mixed liquor volatile suspended solids (MLVSS) was conducted. The POME treatment kinetics were explained with kinetic equations derived by Monod, Contois and Chen and Hashimoto for organic at loading rates within the 1–11 kg·COD·m−3·d−1 range. The UMAS proposed successfully removed 96.6–98.4% COD with a 7.5 day hydraulic retention time. The Y value was 0.67 g·VSS/g·COD, while the specific micro-organism decay rate, b was 0.24 day−1. Methane (CH4) gas production ranged from 0.24 to 0.59 litres per gram of COD daily. Once the initial steady state was achieved, the incoming COD concentrations increased to 88,100 mg·L−1. The three kinetic models recorded a minimum calculated solids retention time of 12.1 days with maximum substrate utilization rate, K values ranging from 0.340 to 0.527 COD·g−1·VSS·d−1 and maximum specific growth rate, µmax from 0.248 to 0.474 d−1. Furthermore, the solids retention time (SRT) was reduced from 500 to 12.1 days, resulting in a 98.4% COD level reduction to 1400 mg·L−1.